Metabolomics and Proteomics of Brassica napus Guard Cells in Response to Low CO2 - Geng, Sisi; Yu, Bing; Zhu, Ning; Dufresne, Craig; Chen, Sixue (Frontiers in Molecular Biosciences, 2017)
Stomatal guard cell response to various stimuli is an important process that balances plant carbon dioxide (CO2) uptake and water transpiration. Elevated CO2 induces stomatal closure, while low CO2 promotes stomatal opening. The signaling process of elevated CO2 induced stomatal closure has been extensively studied in recent years. However, the mechanism of low CO2 induced stomatal opening is not fully understood. Here we report metabolomic and proteomic responses of Brassica napus guard cells to low CO2 using hyphenated mass spectrometry technologies. A total of 411 metabolites and 1397 proteins were quantified in a time-course study of low CO2 effects. Metabolites and proteins that exhibited significant changes are overrepresented in fatty acid metabolism, starch and sucrose metabolism, glycolysis and redox regulation. Concomitantly, multiple hormones that promote stomatal opening increased in response to low CO2. Interestingly, jasmonic acid precursors were diverted to a branch pathway of traumatic acid biosynthesis. These results indicate that the low CO2 response is mediated by a complex crosstalk between different phytohormones.